Patterns of attachment and reflective functioning in families of adolescents with eating disorders - Seah, Elizabeth Jane Izett (Curtin University, 2015)
This study investigated attachment patterns and mentalising capacity of adolescent girls with eating disorders, their mother’s reflective capacity, and family functioning. Girls with eating disorders scored higher rates of insecure attachment, lower attachment coherence and higher hypermentalising than non-clinical girls. Although mothers’ reflective functioning did not differ between groups, a proportion of clinical mothers scored very low reflective functioning compared to controls. Clinical families presented with higher depression, anxiety, communication difficulties and conflict.